Analisis Statis Spacer Adaptor pada Kendaraan Berdisain Khusus M-V3 Seri Komersial - Christofel Jarot Yudaputranto (Jurnal Teknik dan Science, 2025)
Spacer Adaptor is an essential component in vehicle suspension systems, functioning to create space between two mechanical elements to ensure stable and precise connections. This study aims to analyze the structural strength of the Spacer Adaptor on M-V3 vehicle manufactured, using static analysis with SolidWorks software. The simulation was conducted to evaluate the maximum stress and the Factor of Safety (FOS) of the 20 mm design. The results show that the maximum stress is 51.171 N/m², with a FOS value of 13.2. These results indicate that the component has a high safety margin against potential failure due to loading. Therefore, the Spacer Adaptor design is considered highly safe and reliable for tactical vehicle applications.